(untitled) (Superficies y Vacío, 2025)
Hydrogel electrolytes were synthesized using polyvinyl alcohol (PVA) and various graphene derivatives, including graphene oxide (GO), exfoliated graphene (GEX), reduced graphene oxide (rGO), and selectively oxidized graphene (SOG). The effects of these graphene derivatives on the gel structure were analyzed using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and rheological measurements. Additionally, the influence of the water-to-ethylene glycol ratio on the gel properties was assessed. Incorporating graphene derivatives enhanced hydrogen bonding within the hydrogel network, depending on the oxygen functional groups and defect density of the graphene materials, leading to improved structural stability. While ethylene glycol contributes to the gel formation, adding graphene derivatives further enhances the hydrogel’s mechanical properties, maintaining a high storage modulus and preserving ionic conductivity. These findings provide valuable insights for developing supercapacitors with an optimal balance between mechanical strength and energy storage efficiency.